Women’s Access To Justice: Mediation For The Victims of Domestic Violence In Central Java, Indonesia - Sukendar, Sukendar; Saifullah, Muhammad; Sulistiyanto, Priyambudi; Rahman, Luthfi; Ulamai, A. Hasan Asy'ari (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2023)
Most of women victims of domestic violence in Indonesia avoid criminal justice system in resolving their cases because criminal justice system gives financial, psychological, and social burdens for them. They accessed the Religious Court instead and other institutions that implements mediation to resolve their cases. This fact gives wider opportunity for mediation, which is a form of restorative justice system, to be a better alternative dispute resolution for domestic violence cases in Indonesia. Unlike retributive justice system that focuses on punishing the perpetrators, restorative justice system focuses on rehabilitation of the rights of the victims. This research explores mediation conducted by service providers for the victims of domestic violence in the Central Java Province, Indonesia. Data collected through interviews with judges, police, social workers, and religious figures from social organizations. This research found that mediation for the victims of domestic violence has been carried out by the services institutions for the victims of domestic violence both in the court and outside the court. However, not all mediations conducted properly as some mediators both in-court and non-court have not been trained on mediation. There is also a tendency among one service provider to proceed all cases of domestic violence in the criminal court while others want to proceed through mediation, which sparks some internal conflicts among them. This research enriches the literature on the services for the victims of domestic violence and provides some insights for alternative resolution for domestic violence cases in Indonesia and especially in Central Java.